Enabling Collaboration and Communication Across Law Enforcement Jurisdictions: Data Sharing in a Multiagency Partnership - Pickering, Jordan C. (Criminal justice policy review, 2022)
Offenders do not always operate within jurisdictional boundaries and, as such, neighboring law enforcement agencies can benefit from sharing crime data and other investigation-related information with one another, with the shared goal of reducing crime throughout their region. In 2016, one such partnership was formed with seven law enforcement agencies, the District Attorney’s Office, and public health officials in King County, Washington. As part of a larger evaluation of this regional collaboration, the authors assessed the data and intelligence-sharing behaviors of key personnel from each participating agency over an 18-month period. This was done through a series of interviews with key personnel and the use of social network analysis. Results suggest that, although data-sharing networks increased in size and project personnel were able to identify benefits to sharing crime data with one another (e.g., seeing the “bigger picture” regarding crime in their region, using shared crime data to track and combat violent crime), they also identified a number of obstacles associated with cross-jurisdictional data sharing. Findings from this evaluation contribute to the collective understanding and implementation of a regional approach to crime control. If criminal justice agencies plan to work together to reduce crime, data and information sharing are essential. Therefore, it is imperative that agencies are aware of the positive outcomes associated with regional data sharing and the challenges that can arise throughout this collaborative effort.